One-pot synthesis of enantiomerically pure N-protected allylic amines from N-protected α-amino esters - Silveira-Dorta, Gastón; Álvarez-Méndez, Sergio J.; Martín, Víctor S.; Padrón, José M. (Beilstein Journal of Organic Chemistry, 2016)
An improved protocol for the synthesis of enantiomerically pure allylic amines is reported. N-Protected α-amino esters derived from natural amino acids were submitted to a one-pot tandem reduction–olefination process. The sequential reduction with DIBAL-H at −78 °C and subsequent in situ addition of organophosphorus reagents yielded the corresponding allylic amines without the need to isolate the intermediate aldehyde. This circumvents the problem of instability of the aldehydes. The method tolerates well both Wittig and Horner–Wadsworth–Emmons organophosphorus reagents. A better Z-(dia)stereoselectivity was observed when compared to the previous one-pot method. The (dia)stereoselectivity of the process was affected neither by the reaction solvent nor by the amount of DIBAL-H employed. The method is compatible with the presence of free hydroxy groups as shown with serine and threonine derivatives.
Keywords: amino acids; olefination; protecting group free; synthetic methods; Wittig reactions